A practical method for determining shear crack induced deformation in FRP RC beams. (1st November 2016) - Imjai, Thanongsak; Guadagnini, Maurizio; Garcia, Reyes; Pilakoutas, Kypros
Highlights: A simple model to assess shear crack-induced deflections in GFRP RC beams is proposed. Unlike existing models, the proposed model predicts deflection up to beam failure. A fictitious inclined crack simulates the actual individual shear cracks widths. Twelve shear tests on GFRP RC beams were conducted to assess accuracy of the model. The model predicts more accurately the deflection of GFRP RC beams compared to codes. Abstract: This article proposes a practical semi-empirical method for determining shear crack-induced deformations in Glass Fibre Reinforced Polymer (GFRP) Reinforced Concrete (RC) beams. Current design guidelines neglect shear and shear crack-induced deformations in the calculation of deflections of GFRP RC beams. However, shear-induced deformations can be up to 30% of the total beam deflection due to the lower stiffness of GFRP bars compared to steel. To calculate the component of deflection due to shear action and crack opening, the proposed model uses a 'single fictitious inclined crack' with a width equal to the sum of the individual effective shear crack widths. Twelve shear tests were conducted on six RC beams reinforced internally with GFRP bars considering different reinforcement types and test parameters. The additional deformation due to shear cracks calculated by the proposed model is then used to predict the overall deformations of such beams up to failure. It is shown that, in comparison to current design guidelines, the proposed model predicts more accurately the total deflection of FRP RC beams at both service and ultimate loads. This article contributes towards the development of more accurate models to assess the overall shear deflection behaviour of FRP RC beams so as to balance the performance, serviceability and economic viability of structures.